척추 MRI 검사 시 척추 유합술로 인한 금속 인공물 억제 방법에 대한 고찰 - 유세종; Se-jong Yoo; 권순용; Soon-yong Kwon; 김성호; Seong-ho Kim (한국방사선학회 논문지, 2023)
본 연구는 척추 MRI 검사 시 척추 유합술로 인한 금속 인공물을 효과적으로 억제하는 방법을 제시하고자 하였다. 이를 위해 척추 수술용 나사로 제작된 팬텀을 제작하여 금속 인공물을 재현하였다. 그리고 1.5T 그리고 3.0T MRI 장치로 영상을 획득하여 자기장 세기에 따른 금속 인공물의 변화를 평가 하였다. 더불어 수신대역폭을 200, 400, 800 Hz/PX로 증가시키며 금속 인공물을 평가하였다. 그 결과 1.5T MRI 장치에서 획득한 영상에서 발생한 금속 인공물은 3.0T MRI 장치에서 획득한 영상과 비교하여 약 52.2% 감소하여 유의한 차이를 보였다(p< 0.05). 특히, 신호 감쇄 및 신호 누적 영역이 각각 약 52.81%, 42.71% 감소하여 금속 인공물 억제에 큰 효과가 있었다. 반면, 수신대역폭을 200에서 800 Hz/PX까지 증가시키며 영상을 획득한 경우는 1.5T MRI 장치의 경우 최대 8.93%, 3.0T MRI 장치의 경우 최대 10.98% 감소하여 유의미한 효과가 없었다(p >0.05). 본 연구의 결과, 수신대역폭의 증가는 신호 감쇄를 줄여 일부 금속 인공물을 줄였지만 신호 누적을 억제하지 못해 큰 효과가 없었다. 하지만 3.0T에서 1.5T로 자기장의 세기를 줄인 경우, 신호 감쇄와 신호 누적이 크게 감소해 금속 인공물을 효과적으로 개선할 수 있었다. 따라서 척추 유합술로 인한 금속 인공물을 억제하기 위해서는 저 자기장 MRI장치에서 검사하는 것이 가장 효과적인 방법이라고 할 수 있다. This study aimed to present a method to effectively suppress metal artifacts caused by spinal fusion surgery during spinal MRI study. For this purpose, a phantom made of spinal surgery screws was created to reproduce the metal artifact. Then, images were acquired with 1.5T and 3.0T MRI to evaluate changes in metal artifacts according to magnetic field strength. In addition, metal artifacts were evaluated by increasing the receive bandwidth to 200, 400 and 800 Hz/PX. As a result, metal artifacts occurring in images obtained from the 1.5T MRI decreased by approximately 52.2% compared to images obtained from the 3.0T MRI, showing a significant difference (p< 0.05). In particular, the signal loss and signal pile up areas were reduced by approximately 52.81% and 42.71%, respectively, showing a significant effect in suppressing metal artifacts. On the other hand, when images were acquired while increasing the receive bandwidth from 200 to 800 Hz/PX, there was no significant effect, with a decrease of up to 8.93% for the 1.5T MRI and up to 10.98% for the 3.0T MRI (p >0.05). As a result of this study, increasing the receive bandwidth reduced signal loss and reduced some metal artifacts, but did not have a significant effect because it did not suppress signal pile up. However, when the magnetic field strength was reduced from 3.0T to 1.5T, signal loss and signal pile up were greatly reduced, effectively improving the metal artifact. Therefore, in order to suppress metal artifacts caused by spinal fusion surgery, study using a low magnetic field MRI can be said to be the most effective method.